2004
DOI: 10.1590/s0365-05962004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento sistêmico da psoríase - Parte I: metotrexato e acitretina

Abstract: Embora a fisiopatologia da psoríase ainda não esteja totalmente esclarecida e permaneçam dúvidas quanto à natureza dos antígenos que levam à ativação do linfócito T e quanto ao papel dos mecanismos reguladores dos surtos e da resolução da inflamação, são inegáveis os avanços terapêuticos das últimas décadas. Além do surgimento de novos medicamentos, a melhor utilização de tratamentos clássicos e a valorização do impacto da terapêutica na qualidade de vida dos pacientes têm contribuído para a diminuição dos índ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
16
0
6
Order By: Relevance
“…1-3 The economic burden of psoriasis is also a matter of concern to patients due to the permanent cost of treatment and the possibility of lower productivity and absenteeism in the workplace. 4 Therefore, it is currently accepted that the evaluation of disease severity should include clinical, psychological and social factors. 5 …”
Section: Introductionmentioning
confidence: 99%
“…1-3 The economic burden of psoriasis is also a matter of concern to patients due to the permanent cost of treatment and the possibility of lower productivity and absenteeism in the workplace. 4 Therefore, it is currently accepted that the evaluation of disease severity should include clinical, psychological and social factors. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Our study we found that after methotrexate therapy patient's condition was improved. Martins and lucia (2004) in his study stated that MTX still represents a treatment option with good efficacy/cost/tolerance relationship, especially in poorer countries. The final decision of the therapeutic choice for patient with psoriasis should be based on their needs and preferences, but also on the clinical and economic consequences of the therapeutic strategy adopted, and some studies have confirmed a longer remission time and lower cost in rotating treatments with the use of MTX 10 .…”
Section: Methotrexate In Psoriasismentioning
confidence: 99%
“…O ácido fólico (ácido diidrofólico) é ingerido na dieta e o ácido folínico (ácido tetraidrofólico) é usado, efetivamente, pelas vias metabólicas, sendo este o antído-to à superdosagem do metotrexato (Leucovorin cálci-co ® -10mg/m 2 de superfície corporal). 17 A administração de ácido fólico pode ser feita de 1-5mg/dia, sendo 1mg a dose indicada regularmente e 5mg/dia a indicada quando a dose de metotrexato é > 15mg/sem ou quando existem sinais de mielotoxicidade. Em crianças, administrar 1mg/dia em maiores de um ano e 50Ìg/kg/dia em menores de um ano.…”
Section: Metotrexatounclassified